Bagehot for Beginners: The Making of Lending of Last Resort Operations in the Mid-19th Century - Vincent Bignon; Marc Flandreau; Stefano Ugolini (Norges Bank, 2009)
In this paper we survey the development of lending of last resort operations in the mid-19th century. We identify and document critical dimensions of the extension of lending of last resort functions, and also develop original empirical tests enabling us to identify such things as the emergence of "free lending" during financial crisis. Our focus is predominantly on the Bank of England, but we also survey some counterpart evidence for the Bank of France. Our main finding, which extends earlier work (Collins 1992), is that free lending and extensive liquidity support against good collateral developed gradually after 1847 and was already a fact of life before Bagehot published Lombard Street. Another finding is that the extension of the Bank of England's LLR function went along with a reduction of its exposure to default risks, in contrast to accounts that have associated Lending of Last Resort with risk taking or feared, as some contemporaries did, that systematic LLR operations would encourage moral hazard. Finally, we provide a new interpretations of the "high rates" advocated by Bagehot. We suggest that they were meant to prevent banks from free riding on the security offered by the central bank, forcing them to march forward to prevent a market retreat and maintain a critical degree of liquidity.
hdl:11250/2497619
Keywords: E58; G01; N13; 330; Bank of England; Bagehot; Walter; lending of last resort; financial crisis; history of monetary policy